Responding to GPs' information resource needs: implementation and evaluation of a complementary medicines information resource in Queensland general practice - O'Rourke Peter; Myers Stephen P; Janamian Tina; Eastwood Heather (BMC, 2011)
Abstract Background Australian General Practitioners (GPs) are in the forefront of primary health care and in an excellent position to communicate with their patients and educate them about Complementary Medicines (CMs) use. However previous studies have demonstrated that GPs lack the knowledge required about CMs to effectively communicate with patients about their CMs use and they perceive a need for information resources on CMs to use in their clinical practice. This study aimed to develop, implement, and evaluate a CMs information resource in Queensland (Qld) general practice. Methods The results of the needs assessment survey of Qld general practitioners (GPs) informed the development of a CMs information resource which was then put through an implementation and evaluation cycle in Qld general practice. The CMs information resource was a set of evidence-based herbal medicine fact sheets. This resource was utilised by 100 Qld GPs in their clinical practice for four weeks and was then evaluated. The evaluation assessed GPs' (1) utilisation of the resource (2) perceived quality, usefulness and satisfaction with the resource and (3) perceived impact of the resource on their knowledge, attitudes, and practice of CMs. Results Ninety two out of the 100 GPs completed the four week evaluation of the fact sheets and returned the post-intervention survey. The herbal medicine fact sheets produced by this study were well accepted and utilised by Qld GPs. The majority of GPs perceived that the fact sheets were a useful resource for their clinical practice. The fact sheets improved GPs' attitudes towards CMs, increased their knowledge of those herbal medicines and improved their communication with their patients about those specific herbs. Eighty-six percent of GPs agreed that if they had adequate resources on CMs, like the herbal medicine fact sheets, then they would communicate more to their patients about their use of CMs. Conclusion Further educational interventions on CMs need to be provided to GPs to increase their knowledge of CMs and to improve their communication with patients about their CMs use.